Do patients with minimal blunt thoracic aortic injury require thoracic endovascular repair?. Issue 2 (February 2021) - DuBose, Joseph J.; Charlton-Ouw, Kristofer; Starnes, Benjamin; Saqib, Naveed; Quiroga, Elina; Morrison, Jonathan; Gewertz, Bruce; Azizzadeh, Ali
Abstract : INTRODUCTION: The optimal management of minimal blunt thoracic aortic injuries (BTAIs) remains controversial, with experienced centers using therapy ranging from medical management (MM) to thoracic endovascular aortic repair (TEVAR). METHODS: The Aortic Trauma Foundation registry was used to examine demographics, injury characteristics, management, and outcomes of patients with BTAI. RESULTS: Two hundred ninety-six patients from 28 international centers were analyzed (mean age, 44.5 years [SD, 18 years]; 76% [225/296] male; mean Injury Severity Score, 34 [SD, 14]). Blunt thoracic aortic injury was classified as Grade I, 22.6% (67/296); Grade II, 17.6% (52/296); Grade III, 47.3% (140/296); and Grade IV, 12.5% (37/296). Overall aortic-related mortality (ARM) was 4.7% (14/296). Among all deaths, 33% (14/42) were ARM. Open repair was required for only 2%, with most undergoing TEVAR (58.4%) or MM (28.0%). Thoracic endovascular repair complications occurred in 3.4% (6/173), most commonly Type 1 endoleak (2.3%; 4/173). Among patients with minimal aortic injury (Grades I and II), 59.7% (71/119) received MM, while 40.3% (48/119) underwent TEVAR. Two patients initially managed with MM required subsequent TEVAR for injury progression during initial hospital stay. No significant difference in ARM between MM and TEVAR was noted for Grades I and II injuries. CONCLUSION: A third of the trauma victims with BTAI succumb to ARM. Thoracic endovascular repair has replaced open repair but remains equivalent in outcomes to MM for minimal injuries. These data support MM of patients with minimal aortic injury. LEVEL OF EVIDENCE: Therapeutic study, level IV.